1999
DOI: 10.1021/ma981558i
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Dependent Fragmentation of Selectively Deuterated Polystyrenes in ToF−SIMS

Abstract: Two series of monodisperse polystyrenes were synthesized by an anionic polymerization initiated with sec-butyllithium. The number average molecular weights of the macrochains range from 1700 to 93300. The first series consist of deuterated repeat units and hydrogenated end groups (sec-PD8S−H). The other one was fully hydrogenated except for one end group, which was selectively deuterated (sec-PS−D). The sample molecular structures are C4H9(C8D8) n H and C4H9(C8H8) n D, respectively. These polymers were then an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…The first series of peaks More central to this study are the trends observed in moving from low to high molecular weight polymer samples. As observed in other studies of molecular weight trends of polystyrene polymer systems, the intensity of the ions under investigation decrease with increasing molecular weight [16][17][18]. However, the degree of intensity loss over the molecular weight range is different when the systems are analyzed with the Au + or C 60 + primary ion source.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The first series of peaks More central to this study are the trends observed in moving from low to high molecular weight polymer samples. As observed in other studies of molecular weight trends of polystyrene polymer systems, the intensity of the ions under investigation decrease with increasing molecular weight [16][17][18]. However, the degree of intensity loss over the molecular weight range is different when the systems are analyzed with the Au + or C 60 + primary ion source.…”
Section: Resultssupporting
confidence: 64%
“…The depth profiling was performed at room temperature. [16][17][18]26,27]. The spectral data from m/z 5 to 250 shows a typical enhancement of ion intensities as a consequence of using a polyatomic source over a monoatomic source, which ranges in enhancement from 50-to 500-fold.…”
Section: Tof-simsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In this study, PLA oligomer and polymer end-groups are deuterated according to Scheme 1, 20 and compared to non-deuterated PLA to observe the end-group contribution on the surface of the PLA. Similar studies using deuterium labelling have been reported/performed by Shard et al 20 on poly (ethylene glycol) and Vanden Eynde et al 21 on polystyrene. We also use G-SIMS to demonstrate that end-group ions result from a low energetic process (a low T p ), consistent with the requirement for only one bond to be broken to liberate an end-group fragment (main chain fragments require two or more bond scissions).…”
Section: Introductionsupporting
confidence: 81%
“…These methods were used to probe the molecular weight of monodispersed poly(methylmethacrylate) (PMMA) 36 and polystyrene standards. 37,38 In this frame, Vanden Eynde et al also proposed a model of the ion intensity dependencies with the M n of polystyrene polymer chains, which accounted for the influence of end-groups. An effect of the molecular weight was observed up to 130 000 Da.…”
Section: Introductionmentioning
confidence: 99%